Education and training strategic management course to improve students’ self-directed learning and learning outcomes - Imelda Paulina Soko; Damianus Dao Samo (Intelektual Pustaka Media Utama, 2022)
The purposes of this study were: i) Developing strategic management of education and training online tutorial; ii) Testing the feasibility of strategic management of education and training online tutorial; iii) Finding out the obstacles in strategic management of education and training online tutorial development process; and iv) Finding the solutions in overcoming obstacles in developing strategic management of education and training online tutorial. This developmental research used the analysis, design, development, implementation, and evaluation (ADDIE) model and involved second year students of teacher training and education faculty in the Kupang region, Indonesia. The instruments used in this study were: i) Validation guidelines for online tutorial material and supporting instruments; ii) Students’ self-directed learning questionnaire; and iii) Online tutorial formative test questions. Data analysis used descriptive and inferential statistical test. The results show that the online tutorial: i) Fulfilled the aspect of validity in the excellent category; ii) Fulfilled the effectiveness aspect in the good category; iii) Limitations of the source, difficulties in compacting the content of material and developing discussion questions are the obstacles in developing the online tutorial; and iv) The solutions are (utilize Universitas Terbuka (UT)'s open educational resources (OER), make concept maps, and keep practicing to make question samples and consult the questions made to the experts).